Induksi Pertumbuhan Eksplan Endosperm Ulin dengan IAA dan Kinetine - -, HIDAYAT (AGRITROP; Vol. 26, No. 4 Desember 2007)
The aims of this research for examining the effect of concentrations of Indole Acetic Acid (IAA) and Kinetine on the growth of ulin. The research using Murashige and Skoog medium was conducted in Biotechnology Laboratory of Agriculture Faculty, Tanjungpura University from June 2003 to May 2004. All treatments were arranged in randomized complete design with ten treatments and four replications. The variable of this research was scoring on callusformation, time of callusformation (days) and number of callus. The result showed that (5.0 ppm IAA + 6.0 ppm Kinetine) and (6.0 ppm IAA + 5.0 ppm Kinetine) were better concentration combination for callus induction. The better for time of callusformation and numbers of callus were 5.0 ppm IAA + 6.0 ppm Kinetine.
Keywords: IAA, Kinetine, callus, ulin